Measuring macromolecular size distributions and interactions at high concentrations by sedimentation velocity - Chaturvedi, Sumit K. (Nat Commun, 2018)
In concentrated macromolecular solutions, weak physical interactions control the solution behavior including particle size distribution, aggregation, liquid-liquid phase separation, or crystallization. This is central to many fields ranging from colloid chemistry to cell biology and pharmaceutical protein engineering. Unfortunately, it is very difficult to determine macromolecular assembly states and polydispersity at high concentrations in solution, since all motion is coupled through long-range hydrodynamic, electrostatic, steric, and other interactions, and scattering techniques report on the solution structure when average interparticle distances are comparable to macromolecular dimensions. Here we present a sedimentation velocity technique that, for the first time, can resolve macromolecular size distributions at high concentrations, by simultaneously accounting for average mutual hydrodynamic and thermodynamic interactions. It offers high resolution and sensitivity of protein solutions up to 50 mg/ml, extending studies of macromolecular solution state closer to the concentration range of therapeutic formulations, serum, or intracellular conditions.